The serum lipid profile of Parkinson\'s disease patients: A study from the Northwest of Iran - Samira Saedi; Mohsen Hemmati-Dinarvand; Haleh Barmaki; Zohreh Mokhtari; Hadis Musavi; Mohamad Valilo; Ali Mota; Soleiman Mahjoub (Babol University of Medical Sciences, 2021)
Background: Parkinsonchr('39')s disease (PD) is defined as a long-lasting, neurological illness. Low levels of serum lipid fractions are related with a high risk of PD. Current investigation was designed to evaluate the concentration blood lipid fractions in patients suffering from PD and compared with healthy subjects. Methods: This case-control study was conducted from February 2016 to September 2018 in Tabriz University of Medical Sciences, Tabriz, Iran. The present investigation consisted of 75 persons who had PD and 75 normal people. The blood levels of lipid fractions were measured by concentrations of total cholesterol (TC), serum triglycerides (TG), low-density lipoprotein (LDL-C), high-density lipoprotein (HDL-C), and total cholesterol. The results were analyzed with SPSS software using Kolmogorov-Smirnov, chi-square, and studentchr('39')s t-test. Results: Serum level of TG was remarkably lower in patients with PD (111.92±8.75 mg/dL) compared with healthy subjects (123.64±9.97 mg/dL, P=0.008).  Furthermore, we saw an important difference in the level of LDL-C (P=0.001) and TC (P=0.004) between the two groups. However, there was not any observed meaningful difference in the serum concentrations of HDL-C between the studied groups (P=0.135). Conclusion: Our results showed that the serum concentration of TG, LDL-C, and TC are noticeably lower in the PD suffering patients. Further investigations are needed to provide comprehensive information on the participantschr('39') cognitive layout and subsequent actions.